Psychological benefits of the person-nature relationship: a literature review - Hidalgo, Constanza; Rumián, Camila; Saavedra, Camila; Uribe, Tania; Vidal, Anny; Mardones, Rodolfo E. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2021)
The literature reports different benefits of people's relationship with nature. However, for the field of psychology the evidence is partial and not integrated. Consequently, the aim of this paper is to understand the psychological benefits of people's relationship with nature from a systemic review of empirical articles indexed in the Wos, Scopus and Scielo database, between the years 2015 and 2020. We used the PRISMA model for the search, identification and suitability of the articles, which were analyzed in their bibliometric characteristics and thematic content. The main bibliometric findings show that articles produced in the United Kingdom and the United States predominate, conducted in urban natural environments using quantitative methodologies with the use of surveys and physiological measurements. Thematically, we distinguish five dimensions of psychological benefits: restoration of attention, restoration and/or reduction of stress, psychological well-being, mental health and psychosocial benefits. We argue that these benefits are articulated by an activity that mediates people's relationship with nature. We conclude by pointing out the relevance of future research in the Latin American context, the integration of mediating activities and the use of qualitative methodologies.